Bioelectricity Generation From Single-Chamber Microbial Fuel Cells With Various Local Soil Media and Green Bean Sprouts as Nutrient - Mulyono, Tri; Misto, Misto; Busroni, Busroni; Siswanto, Siswanto (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
In this experiment, seven single-chamber microbial fuel cells (MFCs) were made and filled with various types of local agricultural soil and sediments found in irrigation channels, which were mixed with glucose and green bean sprouts mashed as nutrients for microbial survival. MFC electric power was measured every day for 35 days. Every time low electric power indicated weak microbial activity, green bean sprouts were added. The highest electric power of 118 ÂµW (23.4 mW/m2) was observed in fuel cells filled with agricultural land planted with rice. Power density reached the range of 120â€“140 mW/m2, whereas the incubation time showed a maximum of 35 days. This study found that adding green bean sprouts can increase the length of the MFC cycle and strengthen the generated power up to 122 mW.Â